Design and in silico validation of donor DNA for RNA-guided recombinase-mediated knockout of mstnb gene in Labeo rohita - Lukram Sushil Singh; Porkodi Murugesan; Gowhar Iqbal; Nagavara C. Nidarshan; Harini Gunasekaran; Ad. Viralkumar; Kiran D. Rasal; Manoj P. Brahmane; Sunil K. Nayak; Arvind A. Sonwane; Mukunda Goswami (PLoS ONE, 2026)
Myostatin b ( mstnb ), a key negative regulator of skeletal muscle growth, represents a promising target gene for genome editing aimed at enhancing growth performance and aquaculture productivity. The present study aimed to design, construct and in silico validate a donor DNA carrying a single-nucleotide substitution that introduces a premature stop codon in the mstnb gene of Labeo rohita for RNA-guided recombinase (RGR) platform-mediated genome editing. For this purpose the mstnb gene sequence was retrieved from the NCBI database and analysed to identify an appropriate target site within exon 1. A targeted single nucleotide substitution from guanine to thymine (G > T) was strategically planned into the donor DNA upstream of the native stop codon to convert the glycine codon (GGA) into a premature stop codon (TGA). This was achieved by identifying RGR target sites flanking the intended mutation site and designing specific primers to amplify and clone the DNA fragment. The target 600 bp DNA fragment encompassing the mutation site flanked by two RGR target sites was successfully amplified and ligated into the pJET1.2 cloning vector and confirmed through Sanger sequencing. Site-directed mutagenesis successfully introduced the intended nucleotide substitution, which was subsequently confirmed by Sanger sequencing. Computational analyses using InterPro, ColabFold, SWISS-MODEL and CYS_REC predicted that the introduced nonsense mutation would generate a truncated Mstnb protein, resulting in the loss of conserved TGF-β domains, reduced structural stability, and impaired cytokine activity. Structural modelling further revealed disruption of the C-terminal β-sheet structure, reduced stereochemical quality, altered QMEAN Z-scores, and loss of cysteine residues, collectively indicating impaired protein folding and reduced structural stability. These findings suggest that the engineered mutation is likely to abolish the functional activity of the mstnb gene, thereby providing a validated donor DNA construct for precise RGR-mediated genome editing in L. rohita . Future studies will focus on the experimental validation of the engineered donor DNA construct through RGR-mediated genome editing, followed by functional characterization in L. rohita .